Life Shaping, Habits of Mind, and Social Institutions - Maiese, Michelle (Natureza Humana - Revista Internacional de Filosofia e Psicanálise, 2018)
According to the enactivist view of the mind, there is close connection between being alive and being cognitive: to be alive is to be capable of cognitive engagements. The living organism does not passively receive and process stimuli from an external world, but rather helps to determine what counts as useful information on the basis of its structure, needs, and the way that it is structurally coupled with its surroundings. Sense-making is the process whereby it interprets environmental stimuli in reference to its survival needs. However, gauging meaning and significance in a complex social world such as ours goes well beyond mere survival and self-maintenance, and has much to do with adapting and faring well in a specific socio-cultural context. The achievement of human goals requires coordinated movement, which leads to the formation of built-up patterns of engagement and response. Over time, these characteristic patterns of movement and behavior become more engrained and come to comprise an individual’s habitual manner of sense-making. Learning and socialization play a significant role, and habits of mind are formed via interaction with values, cultural norms, and other people. Once habits form and become more engrained, there is a sense in which social norms are internalized and sedimented in the body. Cognition and affectivity therefore are best seen as socially embedded and heavily modulated by relationships and norms. This environmental influence can either (i) cultivate adaptive habits of mind that promote human flourishing, or (ii) contribute to maladaptive habits of mind that alienate people from deep-rooted human needs and interfere with overall well-being. One setting in which habits of mind are profoundly modulated is the college or university. Inside higher educational institutions guided by neoliberal ideology, individuals are habituated to toxic interaction patterns and modes of valuation. Rather than cultivating critical thinking and promoting self-realization, these institutions often undermine such capacities. College and university settings in contemporary neoliberal democracies such as the United States thereby give us a powerful example of how social institutions sometimes serve to cultivate habits of mind that impede human flourishing.